The Object of Islamization of Contemporary Human Knowledge (IOCHK) - Nazia Dinia; Novan Fatchu Alafianta (Tasfiyah: Jurnal Pemikiran Islam, 2022)
The term Islamization is defined in a variable manner by different Muslim intellectuals’ conditional upon their background and field of interest. There are more than twenty Muslim scholars who defined the phrase IOCHK with different connotations, concepts, and theories that one may be complementary to the other and may also opposing one another. This article attempts to analyses and classifies the definition of IOCHK based on the scientific research program of Imre Lakatos and the theory of scientific paradigm of Thomas Kuhn. According to them, there are three pivotal aspects of science: namely Hard Core, Hypothesis and series of theories. The researcher will apply the method of content analysis by comparing, contrasting and classifying different aspects. Using an analytical approach, this paper concludes that there are three main objects of IOCHK: Worldview, Paradigm and Theories or Branch of Knowledge. In addition, the researcher also attempts to resolve the problem of the definition of IOCHK. This could also remove some misunderstandings and unfounded criticisms designated by other Muslim scholars.